Faith, social prestige and violence against surgeon in India and subcontinent: a narrative review - Yagnik, Karan J. (International Surgery Journal, 2021)
Violence against surgeons is universal problem but unique in India. It is reported on a daily basis across India. A lot of literature is available. Analysis and review are required. This article is about the best solutions to violence’s against surgeon. Various books, conference presentation and proceedings, workshop lectures, various electronic databases, symposium lectures, research papers and talks have been selected. Selected full articles were reviewed (total-13 article). This review is conducted for the practical knowledge to prevent violence against surgeon and hence patient-doctor satisfaction. Poor patient surgeon communication and lack of faith in medical system are major reasons for violence. There are more reasons which are discussed in details. Poor image of surgeons, cost of healthcare, poor quality of healthcare and poor communication is major factor for violence against surgeons. Low health literacy and lack of faith in the judicial procedure are also important factor. Media can explain all these things but they are not interested. Surgeon should understand the nature of patient and their relatives and act accordingly. Proper explanation in people’s language can change things in tremendous way.